Vertebral artery injury in major trauma patients in Saudi Arabia: A retrospective cohort study - Chowdhury, Sharfuddin (Sci Rep, 2020)
Blunt vertebral artery injury (VAI) is associated with severe cervicocephalic trauma and may have devastating consequences. This study aimed to determine the incidence and nature of VAI in polytrauma patients. The secondary objective was to assess the association of VAI with previously suggested risk factors. It was a retrospective observational study of all polytrauma patients admitted to the trauma unit between April 2018 and July 2019, who had CT neck angiography to diagnose blunt VAI according to modified Denver criteria. Out of 1084 admitted polytrauma patients, 1025 (94.6%) sustained blunt trauma. Of these, 120 (11.7%) underwent screening CT neck angiography. VAI was detected in 10 (8.3%; 95% CI 4.1–14.8) patients. There were three patients with Grade I injury, two with Grade II, and five with Grade IV injury. Among all trauma admissions, the incidence of diagnosed VAI was 0.9% (95% CI 0.5–1.8). Among patients suspected of VAI, there was no univariable association of VAI with C-Spine fracture: OR 4.2 (95% CI 0.51–34.4; p = 0.18). There were two (20%) deaths related to VAI. Traumatic VAI was uncommonly detected in this major trauma service in Saudi Arabia. High suspicion and liberal screening by CT angiography in cases where VAI is possible should be considered to avoid missed injuries.